2020
DOI: 10.1111/een.12968
|View full text |Cite
|
Sign up to set email alerts
|

Cannibalism and potential predation in larval drosophilids

Abstract: 1. Although yeast encompasses the major food source of Drosophila melanogaster, a recent study demonstrated that D. melanogaster larvae can complete their development on an exclusively cannibalistic diet. If cannibalism is an adaptive behaviour under nutritional stress, not only conspecific larvae but also allospecific larvae could be the target of predation. Under natural conditions, stings of parasitoids can cause a larval injury that attracts cannibalistic larvae, however, the effect of parasitism on larval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Surprisingly though, we found that while lipid reserve was negatively associated with larval density in protein-rich and standard diet (as expected), lipid reserves increased with larval density in sugar-rich diets. The mechanisms underpinning this effect is unclear and there is no evidence of larval cannibalism [as in Drosophila species (Vijendravarma et al 2013;Kakeya and Takahashi 2020)], but it is possible that protein limitation and high intraspecific competition combined triggered stress responses that resulted in individuals having lower body weight but higher lipid storage. In mice, stress is known to stimulate lipid synthesis but deactivate protein synthesis (Fu et al 2011)].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly though, we found that while lipid reserve was negatively associated with larval density in protein-rich and standard diet (as expected), lipid reserves increased with larval density in sugar-rich diets. The mechanisms underpinning this effect is unclear and there is no evidence of larval cannibalism [as in Drosophila species (Vijendravarma et al 2013;Kakeya and Takahashi 2020)], but it is possible that protein limitation and high intraspecific competition combined triggered stress responses that resulted in individuals having lower body weight but higher lipid storage. In mice, stress is known to stimulate lipid synthesis but deactivate protein synthesis (Fu et al 2011)].…”
Section: Discussionmentioning
confidence: 99%
“…Although it is impossible to dismiss the potential for a lab environment to select for cannibalistic individuals, cannibalism has been observed repeatedly across Drosophila spp. (Bhattacharyya, 2015; Kakeya & Takahashi, 2021; Vijendravarma et al, 2013). Also, several of these observations were of individuals that had been collected from the wild only weeks before experimentation (Bhattacharyya, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…For the relatedness trials, a third‐instar victim from the WT and GFP families was selected from their respective ‘early’ vials and each was secured by being impaled on equally sized entomological pins at either end of a 55‐mm diameter Petri dish (15 mm from the centreline) containing agar. Previous work has shown that cannibals are preferentially attracted to injured over non‐injured victims (Kakeya & Takahashi, 2021; Vijendravarma et al., 2013); thus, pinning the larvae likely sped up the onset of cannibalism. Also, pinning the victims in this way ensured that they remained equidistant from the centre of the dish.…”
Section: Methodsmentioning
confidence: 99%
“…In D. melanogaster cannibalism occurs in crowded conditions, where young larvae will attack and consume pre-pupation larvae which are in the 'wandering-stage' (Vijendravarma et al, 2013). Larvae of D. melanogaster and Drosophila simulans Sturtevant (Diptera: Drosophilidae) form aggregations mediated by chemical cues from the injured prey larvae (Kakeya and Takahashi, 2021). The larvae of D. melanogaster and D. simulans are able to sustain themselves, develop normally and reach adulthood on a solely cannibalistic diet, unlike other Drosophila species (Kakeya and Takahashi, 2021;Vijendravarma et al, 2013).…”
Section: Cannibalismmentioning
confidence: 99%
“…Larvae of D. melanogaster and Drosophila simulans Sturtevant (Diptera: Drosophilidae) form aggregations mediated by chemical cues from the injured prey larvae (Kakeya and Takahashi, 2021). The larvae of D. melanogaster and D. simulans are able to sustain themselves, develop normally and reach adulthood on a solely cannibalistic diet, unlike other Drosophila species (Kakeya and Takahashi, 2021;Vijendravarma et al, 2013). Therefore, cannibalistic behaviour is likely not a general feature of the whole Drosophila genus.…”
Section: Cannibalismmentioning
confidence: 99%